Chronometer with luminous display for collective visualization. - Polo, S.; Rodríguez, G.; Flores, P.; Infante, O.; Orta, R. (Revista Mexicana de Ingenieria Biomedica, 1991)
A chronometer was developed to mark the times in conferences, which is easy to visualize. For the design we used an 8031 microcontroller that controls a display and a keyboard for its operation, an optical bar to mark the passage of time emulated an hourglass and a horn to signal the end of time.